2018
DOI: 10.1002/pen.24983
|View full text |Cite
|
Sign up to set email alerts
|

Biocomposite films based on poly(lactic acid) and chitosan nanoparticles: Elaboration, microstructural and thermal characterization

Abstract: Structured and fully bio‐based polymer assemblies based on chitosan micro‐ and nano‐particles and poly(lactic acid) (PLA) were developed using a continuous cast‐film extrusion process. The microstructure and thermal properties of the resulting biocomposite films are studied. Dispersion and size distribution of chitosan particles within the films were analyzed by optical microscopy and laser diffraction. Results show a homogeneous dispersion with no particles agglomeration, due to favorable physico–chemical int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…The behavior of PLAR-1LCh could be explained by the low amount of chitosan and the poor interaction between PLA and this kind of chitosan. However, the reduced viscosity observed in the other composites of PLA and chitosan has not been fully explained, although Hijazi et al (Hijazi et al, 2019) reported that higher amounts of chitosan nanoparticles could contribute to increase the shear stresses during the extrusion, resulting in further degradation of PLA.…”
Section: Intrinsic Viscosity Of the Pla Based Materialsmentioning
confidence: 99%
“…The behavior of PLAR-1LCh could be explained by the low amount of chitosan and the poor interaction between PLA and this kind of chitosan. However, the reduced viscosity observed in the other composites of PLA and chitosan has not been fully explained, although Hijazi et al (Hijazi et al, 2019) reported that higher amounts of chitosan nanoparticles could contribute to increase the shear stresses during the extrusion, resulting in further degradation of PLA.…”
Section: Intrinsic Viscosity Of the Pla Based Materialsmentioning
confidence: 99%
“…[ 20,137‐139 ] PLA is produced from agricultural resources such as corn. [ 140‐143 ] It is a thermoplastic aliphatic polyester with several promising properties such as highly transparency, the capability to be simply degraded, high in strength, stiffness, biocompatibility, thermo‐plasticity, monomer renewability and good processability. [ 127,144‐150 ] Conventional processing methods including injection molding, blow molding, thermoforming and sheet extrusion can be used to process PLA.…”
Section: Polylactic Acid Bionanocompositesmentioning
confidence: 99%
“…[ 151‐153 ] Even so, PLA has low impact strength and is brittle by nature. [ 140,154,155 ] Furthermore, the cost of PLA is more expensive than conventional non‐degradable materials. [ 156 ] Thus, it is still not appropriate for some applications.…”
Section: Polylactic Acid Bionanocompositesmentioning
confidence: 99%
“…Chitosan is a bio‐copolymer, which is formed by N‐acetyl‐D‐glucosamine (acetylated unit) and D‐glucosamine (deacetylated unit), bounding by β‐1–4 bonds (Hijazi et al., 2019; Lopatina & Tsarkova, 2019; Mirsadeghi et al., 2019; Neto et al., 2019). This biopolymer is obtained from the deacetylation of chitin presents in the exoskeleton of crustaceans (Chein, Sadiq, & Anal; Piedrahíta Márquez et al., 2019; D. Yu et al., 2018).…”
Section: Introductionmentioning
confidence: 99%